2002
DOI: 10.4049/jimmunol.168.4.1831
|View full text |Cite
|
Sign up to set email alerts
|

Innate Direct Anticancer Effector Function of Human Immature Dendritic Cells. II. Role of TNF, Lymphotoxin-α1β2, Fas Ligand, and TNF-Related Apoptosis-Inducing Ligand

Abstract: Our recent studies have demonstrated that human immature dendritic cells (DCs) are able to directly and effectively mediate apoptotic killing against a wide array of cultured and freshly-isolated cancer cells without harming normal cells. In the present study, we demonstrate that this tumoricidal activity is mediated by multiple cytotoxic TNF family ligands. We determine that human immature DCs express on their cell surface four different cytotoxic TNF family ligands: TNF, lymphotoxin-α1β2, Fas ligand, and TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
2
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 43 publications
(47 reference statements)
10
126
2
5
Order By: Relevance
“…This antitumor activity has recently been attributed to expression of multiple cytotoxic TNF family ligands including FasL (46). Using adenoviral vectors encoding murine FasL, we were able to discriminate between expressions of endogenous and transduced FasL.…”
Section: Discussionmentioning
confidence: 99%
“…This antitumor activity has recently been attributed to expression of multiple cytotoxic TNF family ligands including FasL (46). Using adenoviral vectors encoding murine FasL, we were able to discriminate between expressions of endogenous and transduced FasL.…”
Section: Discussionmentioning
confidence: 99%
“…The finding remains unclear since it contradicts previous findings. 76 Surprisingly, TLR-7/8-activated human blood-derived DCs demonstrated a Ca 2 þ -dependent cytotoxicity toward tumor cells, evoking a granule exocytosis-dependent mechanism. 54 The authors observed that the basal skin carcinoma-infiltrating CD11c þ DCs co-stained for PRF and GZM and DCs isolated from peripheral blood of those cancer patients exhibit cytotoxicity.…”
Section: Killer Dcsmentioning
confidence: 99%
“…72,73 Immature DCs have also been shown to kill freshly isolated tumors. [74][75][76] Although in vitro-derived immature DCs kill target cells very efficiently at low effector/target ratios via an apoptotic mechanism involving DNA fragmentation, mitochondrial dysfunction, and late membrane disruption, the level of cytotoxicity found in the freshly isolated, immature DCs remains low and questionable. 75 To note, while Chen's group 70 demonstrated that the tumor killing by immature DCs is mediated through direct cell-to-cell contact, Vujanovic's group 75 showed, using the same type of immature DCs, that the killing mechanism was mediated by both cell-to-cell contact and soluble mediators.…”
Section: Killer Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we are interested in analyzing the cytotoxic potential of human CBDC stimulated with LPS or IFN-γ against hematological tumor cell lines, and investigating whether the newly described tumoricidal activity, associated with human CBDC, is mediated by cytotoxic TNF family ligands, as reported previously in peripheral blood or bone marrow cells derived-DC. (9) In addition, based on a series of publications, DC exert selective cytotoxic activity toward tumor cells, while demonstrating no cytotoxicity toward normal cells, such as dermal fibroblasts, epidermal melanocytes, mammary epithelial cells and T cell blasts. (10) We presumed that CBDC could act as effector cells to eliminate residual malignant cells after cord blood transplantation in hematologic malignancies.…”
mentioning
confidence: 99%